ORGANIZATIONAL CITIZENSHIP BEHAVIOR: ANTECEDENTS AND THE EFFECT ON EMPLOYEE PERFORMANCE AT A STATE TREASURY OFFICE IN INDONESIA - Purnamie Titisari, Mochammad Farid Afandi, Kukuh Lukiyanto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The objective of this study is to examine and analyze the effect of leadership style, job satisfaction, organizational commitment, personality and organizational culture on organizational citizenship behavior (OCB) and its impact on employee performance. Using simple random sampling, 190 employees were selected from the study population of all 586 employees of the East Java State Treasury Office. Structural equation modeling (SEM) of the data provided results that show that leadership style, organizational commitment, job satisfaction, and personality have a significant effect on OCB. Further, OCB has a significant effect on the employee performance in the State Treasury Services. However, organizational culture has an insignificant effect on OCB. The study results can be used to further improve the employee performance at East Java State Treasury Office in line with bureaucratic reforms. This study also will enrich and complement knowledge on organizational behavior and human resource management for academicians and practitioners.